Tilting Modules in Truncated Categories - Bennett, M.; Bianchi, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We begin the study of a tilting theory in certain truncated categories of modules G(Γ) for the current Lie algebra associated to a finite-dimensional complex simple Lie algebra, where Γ=P+×J, J is an interval in Z, and P+ is the set of dominant integral weights of the simple Lie algebra. We use this to put a tilting theory on the category G(Γ′) where Γ′=P′×J, where P′⊆P+ is saturated. Under certain natural conditions on Γ′, we note that G(Γ′) admits full tilting modules.